Trends of enrolment of U.P. women students - Clemente, Ursula Uichanco (1958)
This study was conducted for the purpose of determining the extent to which the University has grown in enrolment, in so far as women students are concerned, and to inquire into the nature of their upward movement from one curriculum year to the upper curriculum years. The data of the study were obtained from the registration cards of women students on file in the Office of the Registrar for the academic years 1946-1947 through 1956-1957.
Keywords: Women -- Education (Higher) -- Philippines; School attendance -- Statistics; University of the Philippines -- Students